The effect of Ag atom doped Cu@CuO core–shell structure on its electronic properties and catalytic performance: a first principles study. (8th December 2020) - Zhang, Xiao; Zhou, Xiaolong; Guo, Yanxin; Li, Jintao; Hu, Chen; Zhang, Kunhua; Wang, Lihui
Abstract: Density functional theory was used to study the Ag-doped Cu@CuO core–shell structure, electronic properties and catalytic properties. Similar to the undoped Cu@CuO clusters, the Ag doped clusters also retain the core–shell structure. Ag doping increases the charge transfer between surrounding O atoms and Cu atoms and reduces the potential of the core–shell structure, thereby increasing its surface activity. The study of its orbital distribution found that the doping of Ag atoms caused the interaction between the inner Cu core and the outer CuO shell, which changed the electron orbital motion inside the shell. The internal chemical stability of the core–shell material is improved. In addition, Ag atom doping accelerates the decomposition of H2 O2 on Cu@CuO structure and increases its adsorption of small molecules, which indicates that Ag atom doping improves the catalytic performance of Cu@CuO structure.